Test-driven Java development : invoke TDD principles for end-to-end application development - Farcic, Viktor; Garcia, Alex (Computer programmer) (Packt Publishing, 2018)
Test-driven development (TDD) is a development approach that relies on a test-first procedure that emphasizes writing a test before writing the necessary code, and then refactoring the code to optimize it. The value of performing TDD with Java, one of the longest established programming languages, is to improve the productivity of programmers and the maintainability and performance of code, and develop a deeper understanding of the language and how to employ it effectively. Starting with the basics of TDD and understanding why its adoption is beneficial, this book will take you from the first steps of TDD with Java until you are confident enough to embrace the practice in your day-to-day routine. If you're an experienced Java developer and want to implement more effective methods of programming systems and applications, then this book is for you.